Governança pública e silêncios locais: avaliação em profundidade da política de requalificação urbana da orla da Beira-Mar de Fortaleza (CE) a partir de um recorte territorial na área do Mercado dos Peixes do Mucuripe - Vieira, Daniele Ferreira de Almeida (2024)
This research defined as its general objective to evaluate, in depth, the urban requalification policy of the Beira-Mar coastline of Fortaleza - CE, based on a territorial cut in the area of the Mucuripe Fish Market. The theoretical trajectory of the research related the theme of public governance (Borges, 2000; Martins; Marini, 2014; Diniz, 2015; Bonatto, 2018; Soares, 2024) as an instrument capable of balancing the interests of social actors involved in the implementation of an urban public policy (Glass, 1964; Corrêa, 1989; Lefebvre, 2001; Bezerra, 2009; Maricato, 2020), contributing to the transparency and accountability of government actions and the encouragement of social participation Borges, 2000; Dagnino, 2010; Martins; Marini, 2014; Bonatto, 2018; Martins et al., 2018), serving as a basis for the analysis of the analytical axes of Rodrigues' in-depth evaluation. (2008) in the dimensions of content, context, trajectory, temporality and territoriality of the policy. The research is qualitative in nature, with data collection based on bibliographic and documentary research, as well as semi-structured interviews (Minayo; Deslandes, 2008) carried out with a fisherman, a concessionaire from the Market box and a manager from the Tourism Department. The data were analyzed based on documentary and discourse analysis (Orlandi, 2009). The results indicate the following findings: (i) in the context of the policy content, little integration was observed between the set of standards that guided the implementation process of the Fish Market requalification policy and its planning and execution, resulting in problems in the final result of the work; (ii) in the context of the policy, it was observed that the implementation process of the Fish Market requalification prioritized the development of tourism to the detriment of the less privileged classes, with little transparency and participation of the social actors involved; (iii) within the scope of the institutional trajectory of the policy, it was noted that the requalification of the Fish Market was important for the economic development of the city, favoring tourism and the generation of employment and income, but it failed to take into account the participation of the affected community and the nuances and limitations of the environment; (iv) within the scope of the temporal and territorial spectrum of the policy, it was noted that the work on the Fish Market had positive impacts such as the appreciation of local traders, the regularization of activities and the improvement of infrastructure, but it negatively impacted the fishing community that lost space.